Lactate promotes myogenesis via activating H3K9 lactylation‐dependent up‐regulation of Neu2 expression - Weilong Dai; Gang Wu; Ke Liu; Qianqian Chen; Jingli Tao; Honglin Liu; Ming Shen (Wiley, 2023)
Abstract Background Lactate, a glycolytic metabolite mainly produced in muscles, has been suggested to regulate myoblast differentiation, although the underlying mechanism remains elusive. Recently, lactate‐mediated histone lactylation is identified as a novel epigenetic modification that promotes gene transcription. Methods We used mouse C2C12 cell line and 2‐month‐old male mice as in vitro and in vivo models, respectively. These models were treated with lactate to explore the biological function and latent mechanism of lactate‐derived histone lactylation on myogenic differentiation by quantitative real‐time PCR, western blotting, immunofluorescence staining, chromatin immunoprecipitation, cleavage under targets and tagmentation assay and RNA sequencing. Results Using immunofluorescence staining and western blotting, we proposed that lactylation might occur in the histones. Inhibition of lactate production or intake both impaired myoblast differentiation, accompanied by diminished lactylation in the histones. Using lactylation site‐specific antibodies, we demonstrated that lactate preferentially increased H3K9 lactylation (H3K9la) during myoblast differentiation (CT VS 5, 10, 15, 20, 25 mM lactate treatment, P = 0.0012, P = 0.0007, and the rest of all P < 0.0001). Notably, inhibiting H3K9la using P300 antagonist could block lactate‐induced myogenesis. Through combined omics analysis using cleavage under targets and tagmentation assay and RNA sequencing, we further identified Neu2 as a potential target gene of H3K9la. IGV software analysis (P = 0.0013) and chromatin immunoprecipitation‐qPCR assay (H3K9la %Input, LA group = 9.0076, control group = 2.7184, IgG = 0.3209) confirmed that H3K9la is enriched in the promoter region of Neu2. Moreover, siRNAs or inhibitors against Neu2 both abrogated myoblast differentiation despite lactate treatment, suggesting that Neu2 is required for lactate‐mediated myoblast differentiation. Conclusions Our findings provide novel understanding of histone lysine lactylation, suggesting its role in myogenesis, and as potential therapeutic targets for muscle diseases.